Body ground red – integrating Peirce, Kristeva and Greimas - Tamminen, Herman (Sign Systems Studies, 2020)
Ground (Charles Peirce’s concept) – regardless whether it be taken as motivation or abstractness – affords the proposition that some abstract categories of meaning have acquired their qualities via bodily experience. In order to show this to be the case, the concept of ground will be drawn together with the division (according to Julia Kristeva) between the symbolic and the semiotic, the semiotic chora will be shown to function as an axiologizing thymic category as regard reception of perception (following Algirdas Greimas), and finally it will be proposed that it is this foundation that enables the coherence and inevitability of culture as a whole, being responsible for its stereoscopic quality as well. This procedure will further the haply sacrilegious march towards the emergence of modal semiotics, which allows us to dispense of signs in order to gain an anachronistically novel understanding of our own being.